Communicate! - Verderber, Kathleen S., 1949- 4 0; Verderber, Rudolph F.,;Sellnow, Deanna D.; 5 (Singapre : Cengage Learning Asia, 2014)
This practical text introduces students to the basic process of human communication, emphasizing skills and encouraging students to evaluate themselves and set goals to master those skills
Unit 1. Foundations of communication --- Unit 2. Interpersonal communication and relationships --- Unit 3. Group communication --- Unit 4. Public speaking
Includes bibliographical references (pages 473-491) and index
Keywords: 2 -- 0; 6; Textbooks;Study and teaching -- Communication;Communication;Communication;Misinformation;Communication;Interpersonal Relations;Misinformation -- 20; 20; 2